STUDY DOSE DISTRIBUTION OF PROTON PARTICLES ON BREAST CANCER - YANGKI SULAEMAN (NIM : 20215034), MUHAMMAD
Cancer is a disease that causes abnormalities in normal cell, causing dividing continuously and disrupting surrounding tissue. One type of cancer is breast cancer and tends to attack women more often. There are several methods to treat cancer, one of them is using radiation particles or called radiation therapy and one of the best method to cure cancer. However, recent research on radiotherapy in left breast cancer indicates that there are patients suffering from heart disease and pneumonia after undergoing radiotherapy that use photon particles. It caused by exposure to radiation that penetrates to the back of the breast and irradiates the organ behind it, the heart and lungs. Research on radiotherapy continues to grow, especially in the use of particles other than photons. Recent research discusses proton particles that have different characteristics with other particles, so in this thesis will be discussed about radiotherapy using proton particles, or called proton therapy. In this thesis, breast phantom will be developed with additional rib bone, heart, and lungs as organ at risk with help of computational method toolkit Monte Carlo called GEANT4. Two particles were tested on the phantom, photons with 18 MV energy and protons with three different energies, 80, 120, and 150 MeV. The simulations show that proton particles with energy 80 and 120 MeV do not give doses to three other organs, unlike photons that still irradiate three other organs. The next simulation, tumor model will be added to the breast phantom with 8.5 cm depth and it given proton particles with 120 MeV energy. It shows that the proton able to give big doses to the target and give zero dose to the ribs, heart, and lungs.